Mucosal Grafting Reduces Recurrence After Endonasal Surgery of Petrous Apex Cholesterol Granulomas. (9th February 2021) - Patel, Chirag R.; Snyderman, Carl H.; Fernandez‐Miranda, Juan C.; Gardner, Paul A.; Wang, Eric W.
Abstract : Objectives/Hypothesis: The endoscopic endonasal approach (EEA) is increasingly utilized for management of petrous apex cholesterol granuloma (PACG). Surgical goals include drainage and marsupialization of the cyst. Various techniques have been described to try to reduce the rates of recurrence. We studied the effect of mucosal grafting on recurrence. Study Design: Retrospective Cohort study. Methods: Patients who underwent EEA for PACG at two tertiary care centers between 1999 and 2018 were identified and divided into two cohorts: Mucosal versus no mucosal reconstruction. Surgical approach, reconstructive method, and recurrence were recorded. Primary endpoint was symptomatic or radiographic recurrence. Results: Thirty‐four patients were identified undergoing 37 surgeries. Four patients developed recurrences of which three elected to undergo revision. Some form of mucosa was used to line the drainage tract in 20 cases. A free mucosal graft was used in 8, and a small customized nasal septal flap (miniflap) in 12. All four recurrences occurred in cases where no mucosa was used, demonstrating decreased recurrences with mucosal reconstruction ( P < .05). There was no difference found between free mucosal grafts and miniflaps. Conclusions: Utilization of mucosa to partially line a circumferentially de‐epithelialized drainage pathway after EEA for PACG reduce recurrence rates. Level of Evidence: 3 Laryngoscope, 131:E2513–E2517, 2021